Outlook for the public finances - Carl Emmerson; Martin Mikloés; Isabel Stockton (Institute for Fiscal Studies (IFS), 2023)
In the current environment of high inflation and rising interest rates, tax cuts at the upcoming Budget would be extremely difficult to justify.
Keywords: 330; Government finances and spending; Taxes and benefits; IFS Green Budget 2023; Government spending; Tax; Fiscal rules and frameworks; Fiscal performance